Reciprocal relationships between lexical and syntactic skills of children with Developmental Language Disorder and the role of executive functions. (August 2019) - Blom, Elma; Boerma, Tessel
Background and aims: Recent research indicates that children with Developmental Language Disorder (DLD) often also score lower than their peers with typical development (TD) on tasks testing nonverbal executive functioning (EF). This study investigated whether there is evidence that children with DLD use linguistic and EF resources to support their lexical and syntactic development. Three questions were addressed: (1) How do children with DLD develop in the domains of lexicon and syntax, and how does their development compare to TD controls? (2) To what extent do children with DLD show reciprocal relations between lexical and syntactic skills, and how does this compare to TD controls? (3) Is EF ability related to DLD children's lexical and syntactic skills, and how does this compare to TD controls? Methods: Data from 117 children (NDLD = 78; NTD = 39) were collected three times with yearly intervals. At time 1, the children were 5 or 6 years old. Standardized receptive vocabulary and sentence repetition tests measured lexicon and syntax, respectively. Nonverbal EF tasks tested selective attention, interference control and working memory. Cross-lagged analyses were conducted to determine the direction of relationships. Results: Both groups showed stable lexical and syntactic growth. In children with DLD, but not in TD controls, syntactic skills predicted lexical skills. In the DLD group, EF predicted lexical skills. Reversely, in the TD group, lexical skills predicted EF. Conclusions: The results of this study are consistent with the hypothesis that the lexical development of children with DLD is supported by both their verbal abilities in the domain of syntax and their nonverbal EF abilities. Implications: Interventions that improve the syntactic and EF abilities of children with DLD may have spreading effects and positively impact on word learning by children with DLD.